Sensory characteristics and acceptance of caprine cheese as an incentive to the consumption of goat milk products in Brazil - Benevides, Selene Daiha; Garruti, Deborah dos Santos; Laguna, Luis Eduardo; do Egito, Antônio Silvio; dos Santos, Karina Maria Olbrich; Deliza, Rosires; Queiroga, Rita de Cássia Ramos do Egypto (Science & Technology Journals, 2021)
Producers of goat cheese have been demanding new technologies to diversify products derived from goat milk, aiming to increase their consumption. Therefore, the objective of this work was to evaluate the sensory acceptance of different types of goat milk cheese in three Brazilian capital cities. The cheese types were subjected to sensory characterization using the check-all-that-apply method (CATA). Three different types of goat milk cheeses were elaborated using two varieties of rennet and a creamy probiotic. One of the coalho type cheese was elaborated with the incorporation of pequi oil (pequi is a fruit with a high content of unsaturated fatty acids, carotenoids, and antioxidants). The other coalho type cheese was matured and smoked, which gaves it a yellow color and a characteristic smoked flavor. The creamy cheese with probiotics was developed to serve consumers demanding healthy products with functional appeal. The sensorial characterization and the acceptance of the cheeses were accomplished through the application of the hedonic scale and the check-all-that-apply test (CATA). The results indicated a good acceptance of the three cheese types and the potential for their production and marketing, which meets the demand of both producers and consumers of milk and goat cheese. The CATA test is a promising tool that helps with the development of goat dairy products for the analysis of sensory characteristics and consumer perceptions, and it can contribute to adding a high value for this food segment marketing.